PENGARUH LAMA PENYIMPANAN DAN KONSENTRASI NATRIUM BENZOAT PADA SUHU BERBEDA TERHADAP KADAR VITAMIN C CABAI MERAH (Capsicum annuum L.) DAN SUMBANGSIHNYA PADA MATERI ZAT-ZAT MAKANAN DI KELAS XI MA/SMA - Zainal Berlian; elfira Rosa Pane; mardiana mardiana (Bioilmi: Jurnal Pendidikan, 2015)
Red chilli (Capsicum annuum L.) is one of vegetables that useful for Indonesian people. Red chilli contains high vitamin C (ascorbic acid) and beta-carotene that surpass fruits often consumed by people like papaya, mango, pineaple and watermelon. Red chilli easily rotten so scientist use sodium benzoate to preservate anti-fungi. Red chilli which use sodium benzoate stored in 10oC (freezer) with variate in one day, 5 days and 10 days saving. This research point is to know the impact of sodium benzoate, saving time, saving in the room teperature and saving in the freezer to the red chilli vitamin C level. This research is held in the Politeknik Kesehatan Palembang Jurusan Gizi Laboratory. The decision of the vitamin C level based on the iodin titration. This research used completely randomized design with 8 treatments, 3 replications and 3 saving times till we get 72 trials. These treatments are A1= 0%/100g, A2= 0,07%/100g, A3= 0,09%/100g, A4 = 0,1%/100g, B1= 0%/100g, B2= 0,07%/100g, B3= 0,09%/100g, dan B4= 0,1%/100g which each saved one day, 5 days and 10 days in the room teperature and freezer. This research result show that saving time treatment have real impact to the red chilli vitamin C level is F count 238,57 more than 3,30 in the F table. In the adding concentration treatment sodium benzoate doesn‟t have the real impact to the red chilli vitamin C level that F count 0,023 less than 3,49 in the F table. The temperature treatment doesn‟t also have the real impact to the red chilli vitamin C level that F count -0,0008 less than the 18,51 in the F table. This research higest vitamin C level in the adding sodium benzoate 0,07% treatment which save in the room temperature since from H0 until H+10 the vitamin C level is increassy.